Revisão Taxonômica de Scirtes Illiger, 1807 (Coleoptera: Scirtidae) do Brasil e informações biológicas sobre a família - Melo, Gabrielle de (Entomologia, 2024)
Scirtidae was described by Fleming (1821), and it includes 95 genera, more than 1,900 species, and has a wide geographical distribution. In Brazil, there are 5 genera, 53 species, and 3 subspecies. The larvae of Scirtidae are aquatic, occupying various types of habitats, and the adults are terrestrial, living in riparian vegetation. Scirtidae is a family of Coleoptera that lacks taxonomic, biological, and ecological studies, especially in South America and Africa. Most Neotropical species have brief descriptions, without illustrations or morphological details considered important for identification, such as genitalia, for example. Given the evident taxonomic gap concerning species in this family, the objective of this study is to reduce the existing taxonomic impediment in Scirtidae in the Neotropical region and to contribute biological information about the family. This thesis is organized into three chapters. Chapter I reviews the Brazilian species of Scirtes and describes a new species based on larvae and adults (male and female). Keys for identifying adult males and females of Scirtes and a map with the geographical distribution of the species were developed. Chapter II describes a new jumping genus of Scirtidae for Brazil, based on a species previously allocated in Scirtes, and two new species. This chapter presents information about larvae associated with adults (male and female) and the habitats of the species. Chapter III gathers biological information about Scirtidae, focusing on the Amazon. This chapter addresses the types of habitats and microhabitats where Scirtidae larvae are found, different collection methods, a new method for rearing larvae in the laboratory, new records, and a distribution map of the family in the Brazilian Amazon. This study adds taxonomic information about Scirtidae, reducing the taxonomic impediment of the family in the Neotropical region, enabling the identification of known Scirtes species, and allowing the identification of possible new species of this genus in Brazil.
Taxonomia de Scirtes (Coleoptera: Scirtidae) do Brasil
Keywords: Scirtinae; Taxonomia